INTERPRETATION AND STUDY OF THE EUPHEMIA PHENOMENON - Kabilova Sayyora Abdukarimovna (Western European Studies, 2025)
For a long time, euphemism has been a subject of such disciplines as stylistics, cognitive linguistics, sociolinguistics, as well as linguistics and cultural studies. The term «euphemism» is taken from the Greek language and means «to speak well». The history of the phenomenon of euphemism began long before the formation of linguistics, and even before the emergence of the term euphemism, there was a practice of replacing unpleasant and rude words with softer expressions. This phenomenon was widely used during the development of schools of rhetoric in ancient times as softening and replacing unpleasant, rude words
Keywords: interpretation; linguistic phenomenon; euphemism